2022
DOI: 10.1002/ejoc.202101553
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Oxygen‐Doped PAH Electrochromes: Difurano, Dipyrano, and Furano‐Pyrano Containing Naphthalene‐Cored Molecules (Eur. J. Org. Chem. 2/2022)

Abstract: The Cover Feature shows the color changes achieved, upon oxidation, by newly synthesized electrochromic oxygen‐doped small molecules. The crucial moieties are furano and pyrano. Incorporation of these groups into other organic molecules can be used to greatly expand the library of electrochromic small molecules, giving very good control over color transition observed. Such controlled color changes could take electrochromism from the niche applications it currently occupies, to the wider world. Cover design by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The monomer CZ-FSQ and CZ-FEQ were obtained by Suzuki-coupling reaction. 1 H NMR spectra and mass spectra confirmed that the target molecules were obtained correctly. The synthesis and characterization details of the target molecules and their precursors are shown in the experimental section.…”
Section: Synthesissupporting
confidence: 54%
See 4 more Smart Citations
“…The monomer CZ-FSQ and CZ-FEQ were obtained by Suzuki-coupling reaction. 1 H NMR spectra and mass spectra confirmed that the target molecules were obtained correctly. The synthesis and characterization details of the target molecules and their precursors are shown in the experimental section.…”
Section: Synthesissupporting
confidence: 54%
“…Finally, 0.45 g of white solid was obtained in 28% yield. 1 3 mmol), K 2 CO 3 (0.64 g, 4.6 mmol), and 18-Crown-6 (5% mol) in a 100 mL twoneck round bottom flask under N 2 protection. Then acetone (50 mL) was injected with a syringe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations